Determinants of Firm Value in the Banking Subsector Listed on the Indonesia Stock Exchange: The Role of Financial Ratios and Dividend Policy - Ni Komang Noviyanti (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2026)
Firm value reflects market perceptions of a company’s performance and future prospects. This study examines the influence of financial ratios and dividend policy on firm value in the Indonesian banking subsector. The population of this study comprises all banking companies listed on the Indonesia Stock Exchange (IDX), with a research sample consisting of 45 banks observed over the 2022–2024 period, resulting in balanced panel data. The data used are secondary data obtained from published annual reports and official IDX documentation. Data analysis was conducted using panel data regression techniques, including model selection through the Chow test and Hausman test, followed by estimation using the Fixed Effects Model with Feasible Generalized Least Squares (FGLS) to address heteroskedasticity and cross-sectional dependence. The results indicate that profitability, liquidity, and capital adequacy play essential roles in enhancing firm value, whereas firm size and dividend policy exhibit a negative effect on market valuation, and credit risk shows no significant impact. These findings suggest that strong internal fundamentals and efficient financial management are crucial in strengthening investor confidence and improving firm value within the Indonesian banking industry.